APPROPRIATE GROWTH MODEL DESCRIBING SOME TESTICULAR CHARACTERISTICS IN NORDUZ MALE LAMBS - K. Karakuş; E. Eyduran; T. Aygün; K. Javed (Journal of Animal and Plant Sciences, 2010)
The objective of this study was to determine the appropriate non-linear function describing growth of some testicular traits (testicular length, testicular diameter, scrotal circumference and scrotal length) in Norduz male lambs. Testicular characteristics at 90, 110, 130, 150, 170, and 190 days of age for all the lambs were measured. Four growth (Monomolecular, Logistic, Gompertz, and Richard’s) models were used to explain relationship between each testicular trait-age. Growth models were based on averages of measurements on their testicular traits in each period of all the male lambs. As a result, appropriate growth models explaining growth at early age of testicular length, testicular diameter, scrotal circumference and scrotal length in Norduz male lambs were Logistic and Richard’s non-linear model. Also, age and body weight had significant effect on these testicular traits.
Keywords: Growth models; testicular traits; Norduz male lamb